Bioethical issues in health care quality decision making - Rico Jaime, Víctor Manuel; Domínguez Márquez, Octaviano (Acta Bioethica, 2010)
An interdisciplinary study on bioethics is carried out, regarding health care field and its total quality attributes, with focus in decision making, integrating the main bioethical issues –dignity, autonomy and responsibility- as unavoidable components in decisions geared to continuous total quality improvement in the vast field of medical care. This is an analytic study which puts forward the enormous need to relate in a interdisciplinary way health care services management and some bioethical issues hidden or with little visibility, with the intention of improving awareness of them objectively and to be included in design and consequences estimated though specific indicators.